Pengaruh Senam Ergonomis terhadap Tingkat Kemandirian Activity of Daily Living pada Lansia - Puspaningrum, Wida; Kurnia, Rina (Politeknik Kesehatan Kemenkes Surakarta, 2024)
Background: Aging is a natural process in the elderly which causes changes in health, physical, mental and social. This will have an impact on the independence of the elderly in their Activities of Daily Living (ADL). Activity of Daily Living (ADL) is a form of measuring a person's ability to carry out daily activities independently. One important measure of morbidity (unwell condition) is a person's ability to perform ADLs. Ergonomic exercise is an effort to address the problem of elderly independence in carrying out daily activities independently. Objectives: The purpose of this study was to determine the effect of ergonomic gymnastics on the level of independence in the Activity of Daily Living in the elderly in Balak Village, Cawas District, Klaten Regency. Methods: This research is a quantitative research with a one group pre- test post-test design. Ergonomic gymnastics was carried out as many as 12 sessions in 8 weeks. This research sampling method uses a purposive sampling technique of 30 samples. The research instrument used is Functional Independence Measurement (FIM). Data analysis using SPSS version 25 with statistical Wilcoxon test technique. Results: Based on the results of data analysis, the sample is dominated by men (60%). The education level of respondents is mostly elementary school (66.7%). The highest age is at 60 – 74 years (83.3%). The majority of respondents lived with their families (86.7%). The status of couples is dominated by those who have a partner (76.7%). BMI is dominated by those with normal weight (46.7%). The results of the study averaged the level of independence of the elderly before the intervention was 105.1 and after the intervention of ergonomic gymnastics became 114.4 which means there was an increase. Wilcoxon test results obtained a p-value of 0.000. Conclusion: Ergonomic gymnastics affect the level of independence in the Activity of Daily Living for the erderly in Balak Village, Cawas District, Klaten Regency. Keywords: Ergonomic Gymnastics, level of independence, Elderly.